1997
DOI: 10.1016/s0029-7844(97)00111-7
|View full text |Cite
|
Sign up to set email alerts
|

Absorption kinetics of misoprostol with oral or vaginal administration

Abstract: There are significant differences in the pharmacokinetics of misoprostol administered by vaginal and oral routes that may explain the difference observed in clinical efficacy. Assuming that the pharmacologic effect of misoprostol is related to its concentration in the plasma, our observation of the prolonged serum concentrations in the vaginal group suggests that vaginal administration could be dosed at longer intervals than oral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
292
1
22

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(324 citation statements)
references
References 15 publications
9
292
1
22
Order By: Relevance
“…13 Drug absorption after vaginal administration varies widely. 9,14 In an observational study, Zalanyi 15 moistened the tablets with saline solution and reported expulsion in 88% of women with anembryonic or embryonic/fetal death pregnancies. Perhaps the addition of saline solution to the tablets enhanced the drug's effectiveness.…”
mentioning
confidence: 99%
“…13 Drug absorption after vaginal administration varies widely. 9,14 In an observational study, Zalanyi 15 moistened the tablets with saline solution and reported expulsion in 88% of women with anembryonic or embryonic/fetal death pregnancies. Perhaps the addition of saline solution to the tablets enhanced the drug's effectiveness.…”
mentioning
confidence: 99%
“…6,7 The temperature elevations associated with misoprostol appear to be associated with shift in the hypothalamic set point as prostaglandins have been known to be associated with endogeneous fever mechanisms. 7 High fever reported in our patient appears to be related to misoprostol rather than infection despite the fact there was leukocytosis. This may be explained due to the fact that there were no further spikes of fever and total leucocyte count dropped down to normal within next few hours.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios norteamericanos comparan el manejo médico con dosis oral única de 400 µg de misoprostol contra igual dosis oral cada 4 horas, obteniendo tasas de éxito del 13% versus 50-70% respectivamente (14). La administración oral parece ser tan efectiva como la administración vaginal, pero se asocia con más efectos secundarios, probablemente relacionadas con diferencias en la farmacocinética (15).…”
Section: Discussionunclassified